Genetic disenhancement and xenotransplantation: diminishing pigs’ capacity to experience suffering through genetic engineering - Rodger, Daniel (Journal of medical ethics, 2024)
One objection to xenotransplantation is that it will require the large-scale breeding, raising and killing of genetically modified pigs. The pigs will need to be raised in designated pathogen-free facilities and undergo a range of medical tests before having their organs removed and being euthanised. As a result, they will have significantly shortened life expectancies, will experience pain and suffering and be subject to a degree of social and environmental deprivation. To minimise the impact of these factors, we propose the following option for consideration—ethically defensible xenotransplantation should entail the use of genetic disenhancement if it becomes possible to do so and if that pain and suffering cannot be eliminated by other means. Despite not being a morally ideal ‘solution’, it is morally better to prevent unavoidable pain until a viable non-animal alternative becomes available.